Reporting Expertise in Agricultural Communications, Education, Extension, and Leadership Research: The Development of an Expertise Rubric - Lori M Costello; Billy R McKim; Allison L Dunn (Journal of Applied Communications, 2023)
This exploratory quantitative study assessed 149 behaviors, characteristics, and techniques considered indicative of expertise to determine what social scientists in Agricultural Communications, Education, Extension, and Leadership (ACEEL) disciplines value. A total of 731 social scientists from 25 land-grant universities across the United States surveyed in the fall of 2018 served as the population for this study. Using Principal Component Analysis (PCA), 10 constructs describing expertise were identified. A list of the 10 constructs was presented to faculty representing the ACEEL disciplines who helped determine what the constructs collectively measured, resulting in a label for each construct. The behaviors, characteristics, and techniques of the highest scoring constructs were used to create a rubric to assist social scientists in the systematic and intentional selection and description of the qualifications and expertise of individuals asked to serve as coders (Content Analysis), expert panelists (the Delphi method), and any contributor to social science studies in ACEEL disciplines. Use of the rubric would improve the overall consistency and transparency in how qualifications of expertise are reported in academic publications.
Keywords: Expertise; Expert; Content Analysis; Delphi; Rubric